PENERAPAN KEGIATAN KOKURIKULER BERBASIS SENI DAN BUDAYA LOKAL DALAM MENANAMKAN NILAI PENDIDIKAN KARAKTER PADA MURID KELAS IV SD NEGERI 5 SUMERTA DENPASAR - I Putu Nanda Saputra; I Gede Sedana Suci; Ni Nyoman Tri Wahyuni (STKIP Subang, 2026)
This study is motivated by the importance of instilling character education values through learning activities based on local culture. Co-curricular activities based on local arts and culture are considered effective in fostering character values through active and meaningful learning experiences. This study aims to describe the implementation of co-curricular activities based on local arts and culture in instilling character education values in fourth-grade students of SD Negeri 5 Sumerta Denpasar. This study employed a descriptive qualitative approach involving teachers and fourth-grade students of class IVB at SD Negeri 5 Sumerta Denpasar as the research subjects. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to obtain an in-depth understanding of the implementation of the activities. The results showed that the co-curricular activities were implemented through painting activities that actively involved students in the learning process. The character values developed were creativity and independence. Creativity was reflected in students’ ability to express ideas and produce artworks, while independence was demonstrated through their ability to prepare tools and materials, complete their work independently, and take responsibility for the results. The implementation of the activities was supported by students’ enthusiasm and the teacher’s role; however, it still faced obstacles such as limited time and differences in students’ abilities in creating artworks.